Evaluación de un extracto de algas marinas (Green marine powder) en el crecimiento de dos variedades de arándanos (Biloxi y Emerald), provincia Tungurahua, cantón Ambato, 2023 - Poma Tituaña, Gioconda Jacqueline (2024)
The current research work was made in the Tungurahua province, Ambato canton, Montalvo parish, with the purpose by assessing a seaweed extract use (Green marine powder) for the growth from Blueberry plant (Vaccinium corymbosum L. Var Biloxi. L. Var Emerald.). It was implemented the crop based on the blueberry agronomic management manual by Ing. Abel González. In the experimental design, it was used a completely randomized block design (DBCA) with A x B factorial arrangement, with 6 treatments (T1: B+EA 0gr); (T2: B+EA 0.25gr); (T3: B+EA 0.75gr); (T4: E+EA 0gr); (T5: E+EA 0.25gr); (T6: E+EA 0.75gr) and three repetitions in two varieties, with the same made substrate based rice husk, palm fiber, and activated crushed carbon. The assessed variables were: plant height, basal shoots and lateral shoots. The got result was greater growth in the Biloxi variety, unlike the Emerald variety, which had less growth for the dosage 0.75 gr/water liter 135 days after applying the product. For the basal shoots variable, the Biloxi variety with treatment 3 presented greater sprouting followed by the Emerald variety with treatment 6. For the lateral shoots variable it is treatment 3 (Biloxi variety 0.75gr/water liter) with a sprouts total 39 to 135 days; followed by treatment 6 (Emerald Variety 0.75gr/water liter) with a total of 32 sprouts and the treatment with the fewest lateral sprouts is T4 (Emerald Variety 0gr/liter of water) with 16 sprouts. At the research end, the dose 0.75 gr/water liter presented favorable growth effects in the two varieties from blueberries, while the control was appreciated late plant growth and therefore flowering.